Relasi Interpersonal Relasi Interpersonal Santri Pondok Pesantren Mansyaul Ulum Ganjaran Gondanglegi Malang - Badrul Arifin (Pascasarjana Universitas Al-Qolam Malang, 2024)
Interpersonal Relations refers to the relationships and interactions formed between two or more people. This is one of the important aspects of Interpersonal Relations. This research aims to examine the interpersonal relations of students. The focus of the research is: 1) Identifying the forms of Interpersonal Relations shown by the students, 2) Analyzing the factors that shape the Interpersonal Relations of the students, and 3) Knowing the types of Interpersonal Relations that are prominent among the students. This research uses a qualitative approach, with data collection techniques through observation, interviews and documentation. The results of the research show that: The interpersonal relationships of students at the Mansyaul Ulum Islamic Boarding School reflect positive traits, such as mutual respect, polite silence, mutual help, sensitivity and care for others, and a high sense of gratitude. These interpersonal relationships can be seen in daily activities, such as visiting and caring for sick friends, greeting and kissing the hands of older people. The main factors that shape the interpersonal relations of students are the example and personality of the kiai, which is reflected in discipline, authority, closeness to the students, giving love and advice. According to the kiai, a teacher must be a good role model for his students. The most prominent type of interpersonal relations among students is the tendency to live independently, get along well, be friendly, and comply with Islamic boarding school rules, which can be seen from their polite behavior in daily life at the Islamic boarding school.